Abnormal Respiratory Sounds Classification Using Deep CNN Through Artificial Noise Addition - Zulfiqar, Rizwana; Majeed, Fiaz; Irfan, Rizwana; Rauf, Hafiz Tayyab; Benkhelifa, Elhadj; Belkacem, Abdelkader Nasreddine (Frontiers in Medicine, 2021)
Respiratory sound (RS) attributes and their analyses structure a fundamental piece of pneumonic pathology, and it gives symptomatic data regarding a patient's lung. A couple of decades back, doctors depended on their hearing to distinguish symptomatic signs in lung audios by utilizing the typical stethoscope, which is usually considered a cheap and secure method for examining the patients. Lung disease is the third most ordinary cause of death worldwide, so; it is essential to classify the RS abnormality in an accurate way to overcome the death rate. In this research, we have applied Fourier analysis for the visual inspection of abnormal respiratory sounds. Spectrum analysis was done through Artificial Noise Addition (ANA) in conjunction with different deep convolutional neural networks (CNN) to classify the seven abnormal respiratory sounds – both continuous (CAS) and discontinuous (DAS). The proposed framework contains an adaptive mechanism of adding a similar type of noise to unhealthy respiratory sounds. ANA makes sounds features enough reach to be identified more accurately than the respiratory sounds without ANA. Results obtained are many superiors compared to previous techniques since we considered the seven different classes of abnormal respiratory sound simultaneously.